Digital Divide for Teacher During Pandemic Covid-19 - Qomaruzzaman Azam Zami; Bagong Suyanto (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2021)
The phenomenon of the emergence of corona viruses disease ( covid19 ) in today's world affects change in social life especially from face-to-face models to online learning models. This has led to the emergence of disparities in access to the ability for teachers e-learning Blitar district .The digital gap by Van Dijk suggested that access is high in the communication and information technology categories held by individual persons and a high position. Those with higher education more have access to the internet than those with low. The second is the adoption diffusion theory By Everret M .Rogers were explained the adoption process of technology, information, and communication and discuss how innovation is adopted by the community. This study adopted qualitative approaches through in-depth interviews with five teachers chosen by purposive sampling methods. The results are the differences in resources experienced by teachers have an impact on the duration of access (often using built-in applications but never used for learning), mental, and social (teachers become passive). The most dominant differences in access are differences in motivation (teachers do not have a strong motivation to access), materials (teachers do not have sufficient income to access digital technology every day), skills and usage (teachers are not intense in using digital technology, they do not use current learning applications).